Management of new technology proceedings of a conference organized by the Institution of Civil Engineers and held in London on 19 October 1987. (Thomas Telford, 1988)
As computers spread into more areas of construction, it becomes ever more pressing that their new uses and potential applications should be clearly understood. This book covers many different aspects of computers in the field of the construction industry.
Keywords: Civil engineering -- Data processing -- Congresses.; Technological innovations -- Congresses.; elektronické knihy; electronic books